PRAKTIKALITAS PERANGKAT PERCOBAAN FLUIDA DINAMIS SEBAGAI MEDIA PEMBELAJARAN FISIKA SMA - Wewel Guccia Bakri; Hendar Sudrajad; Zulhelmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The study aims to determine the practicalities of product resulting from the research design and validation devices fluid dynamic experiment that has been done before. The approach used in this study is research and development (R&D). Data was collected through the practicality questionnaire and observation sheet. Respondents of this research were from student , teacher as an observer while student tested produk. The data of instrument were analyzed usingMs. Excel. The value of the practicalities of the experimenti by students is 3.55 and observer value practicalities of the experiment by teachers is 3.54, while the value of the practicalities of the use of guide books by teachers is 3.51 and the value of the practicalities of the use of guide books by students is 3.38. The results of this research indicate that experimental device given ease in studying dynamic fluid, so the device experimental and guide book also practical used student.Keywords: Practicality, experiment device of dynamic fluid